Detection of radical species formed by the ozonolysis of α-pinene - Pavlovic, Jelica; Hopke, Philip K. (Journal of atmospheric chemistry, 2010)
Highly reactive free radical species have been subject of many toxicological in vivo and in vitro studies because of the oxidative cell damage they cause. Similar species have been postulated to be the key intermediates formed during many environmental chamber reactions and atmospheric oxidation of organic species present in the troposphere. Thus, detection and characterization of these transient radical species are important steps in understanding the atmospheric chemistry and confirming the reaction pathways involved in secondary organic aerosol formation. Study of these species is particularly difficult because of their short life-times. To facilitate such studies, 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) and diethyl-(2-methyl-1-oxido-3,4-dihydro-2H-pyrrol-2-yl) phosphonate (DEPMPO) nitrone spin traps were used to capture radicals formed from the α-pinene/ozone reaction. Electrospray ionization/tandem mass spectrometry (ESI/MS n ) was applied to elucidate their structures. Characteristic fragments with m/z 114, m/z 130 and m/z 148 with the DMPO trap, and m/z 236, m/z 252, and m/z 270 with the DEPMPO trap indicated the existence of alkyl, alkoxyl and peroxyl radicals, respectively.